Systems & Control for the future of humanity, research agenda: Current and future roles, impact and grand challenges. (2017) - Lamnabhi-Lagarrigue, Francoise; Annaswamy, Anuradha; Engell, Sebastian; Isaksson, Alf; Khargonekar, Pramod; Murray, Richard M.; Nijmeijer, Henk; Samad, Tariq; Tilbury, Dawn; Van den Hof, Paul
Abstract: Following in the footsteps of the renowned report "Control in an Information Rich World, " Report of the Panel on "Future Directions in Control, Dynamics, and Systems" chaired by Richard Murray (2002), this paper aims to demonstrate thatSystems & Control is at the heart of the Information and Communication Technologies to most application domains . As such, Systems & Control should be acknowledged as a priority by funding agencies and supported at the levels necessary to enable technologies addressing critical societal challenges. A second intention of this paper is to present to the industrials and the young research generation, a global picture of the societal and research challenges where the discipline of Systems & Control will play a key role. Throughout, this paper demonstrates the extremely rich, current and future, cross-fertilization between five critical societal challenges and seven key research and innovation Systems & Control scientific challenges. This paper is authored by members of the IFAC Task Road Map Committee, established following the 19th IFAC World Congress in Cape Town. Other experts who authored specific parts are listed below.